Correlation between C-Reactive Protein to Albumin Ratio and Disease Activity in Patients with Axial Spondyloarthritis. (14th June 2021) - Zhong, Zheng; Huang, Yukai; Liu, Yuqi; Chen, Junming; Liu, Meng; Huang, Qidang; Zheng, Shaoling; Guo, Xin; Deng, Weiming; Li, Tianwang
Abstract : Background . The C-reactive protein (CRP) to albumin (ALB) ratio (CAR) has emerged as a novel inflammatory biomarker. This study was designed to investigate the role of CAR in the disease activity of axial spondyloarthritis (axSpA). Methods . A total of 241 patients and 61 healthy controls were retrospectively enrolled in this study. AxSpA patients were further divided into the inactive group (n = 176 ) and active group (n = 65 ) according to Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) cutoff value of 4. Laboratory data and clinical assessment indices were recorded. Spearman's correlation analysis, receiver operation characteristic (ROC) curve analysis, and binary logistic regression analysis were performed. Results . In axSpA patients, CAR was significantly higher than the healthy group (P < 0.001 ). Similarly, axSpA patients in the active group had higher CAR than the inactive group (P < 0.001 ). Besides, CAR was positively correlated with erythrocyte sedimentation rate (ESR) (r = 0.704, P < 0.001 ), CRP (r = 0.996, P < 0.001 ), BASDAI (r = 0.329, P < 0.001 ), and Bath Ankylosing Spondylitis Functional Index (BASFI) (r = 0.330, P < 0.001 ). ROC curve analysis suggested that the area under the curve (AUC) of CAR for axSpA of the active group was 0.701, which was higher than that of CRP and ESR. The optimal cutoff point of CAR for axSpA of the active group was 0.3644, with a sensitivity and specificity of 58.5% and 79.0%. Binary logistic analysis results revealed that CAR was an independent predictive factor for axSpA disease activity (odds ratio = 4.673, 95% CI: 1.423-15.348, P = 0.011 ). Conclusions . CAR was increased in axSpA and axSpA of the active group. CAR may be a novel and reliable indicator for axSpA disease activity.